Review of the National Examination Policy in the Learning Evaluation Paradigm and its Implications for Madrasah Students - Musnandar, Aries; Salim, Salim (Journal of Noesantara Islamic Studies, 2024)
The National Examination (UN) policy, which has been implemented in Indonesia for a long time, has a number of weaknesses in terms of educational science. The UN is not "a test fits for all" because it is not multifunctional, not suitable and not a test that fits all. The implementation of the UN at the basic education level such as in Madrasah is not appropriate and is not in line with the concept of the latest learning evaluation. As an educational institution that emphasizes its students on Islamic manners and morals in studying, Madrasah actually does not need to evaluate the learning of its students by using UN questions. Therefore, the researcher tried to examine the implications of the UN policy for Madrasahs by using the literature review method in the perspective of the concept of renewable learning evaluation. The results of the study show that the UN policy is unfair, inappropriate and imposed and does not have an adequate theoretical basis, especially based on the concept of learning evaluation. The UN relies more onpaper & pencil tests even though the written test is only a small part of the evaluation aspect of students. Even more so in assessing primary level students in madrasah educational institutions that are characterized by religion.